Contrasting effects of Symbiodinium identity on coral host transcriptional profiles across latitudes. Issue 15 (13th July 2018) - Barfield, Sarah J.; Aglyamova, Galina V.; Bay, Line K.; Matz, Mikhail V.
Abstract: Reef‐building corals can increase their resistance to heat‐induced bleaching through adaptation and acclimatization and/or by associating with a more thermo‐tolerant strain of algal symbiont ( Symbiodinium sp.). Here, we show that these two adaptive pathways interact. We collected Acropora millepora corals from two contrasting thermal environments on the Great Barrier Reef: cooler, mid‐latitude Orpheus Island, where all corals hosted a heat‐sensitive clade C Symbiodinium, and warmer, low‐latitude Wilkie Island, where corals hosted either a clade C or a more thermo‐tolerant clade D. Corals were kept in a benign common garden to reveal differences in baseline gene expression, reflecting prior adaptation/long‐term acclimatization. Model‐based analysis identified gene expression differences between Wilkie and Orpheus corals that were negatively correlated with previously described transcriptome‐wide signatures of heat stress, signifying generally elevated thermotolerance of Wilkie corals. Yet, model‐free analyses of gene expression revealed that Wilkie corals hosting clade C were distinct from Wilkie corals hosting clade D, whereas Orpheus corals were more variable. Wilkie corals hosting clade C symbionts exhibited unique functional signatures, including downregulation of histone proteins and ion channels and upregulation of chaperones and RNA processing genes, putatively representing constitutive "frontloading" of stress response genes. Furthermore, clade C Symbiodinium exhibited constitutive expression differences between Wilkie and Orpheus, indicative of contrasting life history strategies. Our results demonstrate that hosting alternative Symbiodinium types is associated with different pathways of local adaptation for the coral host. These interactions could play a significant role in setting the direction of genetic adaptation to global warming in the two symbiotic partners.